(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper investigates the influence of water temperature on the efficiency of distillate production in solar stills. Solar stills are devices that harness solar energy to purify water through evaporation and condensation processes. Understanding the relationship between water temperature and distillate output is crucial for optimizing the design and operation of these systems. Through a series of controlled experiments, this study quantifies the impact of varying water temperatures on distillate production and provides insights for enhancing solar still performance.